Acceptability and use of a patient-held communication tool for people living with dementia: a longitudinal qualitative study. Issue 5 (5th May 2020) - Leavey, Gerard; Corry, Dagmar Suzanna; Waterhouse-Bradley, Bethany; Curran, Emma; Todd, Stephen; McIlfatrick, Sonja; Coates, Vivien; Watson, Max; Abbott, Aine; McCrory, Bernadine; McCormack, Brendan
Abstract : Objectives: To assess the acceptability and use of a low-cost patient-held communication tool. Design: Longitudinal qualitative interviews at three time points over 18 months and document content analysis. Setting: Primary and community services. Participants: Twenty-eight dyads: People living with dementia in Northern Ireland and their informal carers. Interventions: A patient-held healthcare 'passport' for people living with dementia. Primary and secondary outcomes: Acceptability and use of the passport—barriers and facilitators to successful engagement. Results: There was a qualified appreciation of the healthcare passport and a much more nuanced, individualistic or personalised approach to its desirability and use. How people perceive it and what they actually do with it are strongly determined by individual contexts, dementia stage and other health problems, social and family needs and capacities. We noted concerns about privacy and ambivalence about engaging with health professionals. Conclusion: Such tools may be of use but there is a need for demanding, thoughtful and nuanced programme delivery for future implementation in dementia care. The incentivisation and commitment of general practitioners is crucial. Altering the asymmetrical relationship between professionals and patients requires more extensive attention.